Postnatal growth of preterm infants during the first two years of life: catch-up growth accompanied by risk of overweight - Junyan Han; Yuan Jiang; Jun Huang; Yue Zhang; Ying Zhang; Yi Zhang; Xiaotian Chen; Yun Li; Weili Yan (Italian Journal of Pediatrics, 2021)
Abstract Background Early postanal growth of preterm infants has many effects on early and late health. However, evidence on growth pattern in Chinese preterm infant population during early life is insufficient. This study aims to describe the growth trajectory, catch-up growth, and risk of overweight of preterm infants during the first 2 years of life in a Chinese community population. Methods All preterm infants (n = 10,624) received routine childcare in one primary maternal and child healthcare network in 8 years were included. Body weight and length/height at corrected age (CA) 40 weeks, CA 3 months, 6 months, 9 months, 12 months, 18 months, and 24 months were extracted and converted to z-scores based on the World Health Organization (WHO) standards. According to the intrauterine growth status, infants were divided into small for gestational age (SGA), appropriate for gestational age (AGA), and large for gestational age (LGA) infants. Changes of z-score were used to describe the growth velocity. Generalized estimating equation (GEE) model was used to analyze growth trajectory trends over time. Results Body weight and length/height were overall above the WHO standards during the first 2 years of life. Z-score increased significantly by 0.08 (95% CI: 0.06–0.10) in weight and 0.07 (95% CI: 0.04–0.09) in length/height from CA 40 weeks to 3 months and then levelled off until CA 24 months after adjustment. Almost 90% of AGA and LGA infants achieved growth targets (≥25th percentile of WHO standards), and over 85% of SGA infants achieved catch-up growth (≥10th percentile of WHO standards) before CA 24 months. However, the risk of overweight appeared during this period, with the proportion of infants with the risk of overweight being at the peak at CA 3 months (25.6% of all preterm infants and 39.4% of LGA infants). Growth trajectories of SGA showed increasing trends, but those of LGA showed decreasing trends during the first 2 years. Conclusions Body weight and length/height of preterm infants are above the WHO standards in the Chinese community population during the first 2 years of life. Catch-up growth is accompanied by risk of overweight as early as CA 3 months. (349 words)